AI based failure analysis for one type of transformers in power systems - Xiong, Yifu (Nanyang Technological University, 2023)
Electricity is now required for human productivity and daily existence. Electricity is vital to social, scientific, and technical advancement, among other things. The power system, which transmits and distributes the power produced by the power plant to each consumer, is a crucial component of the power system's transmission, distribution, and consumption. Electricity reliability is crucial for the country as well as the household.